2021
DOI: 10.1002/jgf2.388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diagnostic error cases among Japanese residents using diagnosis error evaluation and research taxonomy

Abstract: The process of diagnostic errors among Japanese residents has not been previously studied. This descriptive study was conducted in June 2019 on junior residents at a single‐center educational hospital in Japan. Diagnosis Error Evaluation and Research taxonomy was used to measure the process of diagnostic error in the most memorable error cases. High frequency of diagnostic errors resulted from inaccurate/misinterpretation of history, failure/delay in eliciting physical examination findings, inaccurate/misinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The disease recalled from the medical history information will affect the subsequent physical examination and laboratory tests to be undertaken. Previous reports have acknowledged that diagnostic errors are likely to occur at this point [6].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The disease recalled from the medical history information will affect the subsequent physical examination and laboratory tests to be undertaken. Previous reports have acknowledged that diagnostic errors are likely to occur at this point [6].…”
Section: Discussionmentioning
confidence: 94%
“…Most diagnostic errors likely occur during information collection and integration [5]. Japanese residents are prone to making diagnostic errors during history-taking, physical examination, and assessment [6]. Furthermore, 32% of diagnostic errors occur when integrating information from medical history, physical examination, and assessment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic errors, defined as "the failure to (a) establish an accurate and timely explanation of the patient's health problem(s) or (b) communicate that explanation to the patient," are common worldwide patient safety issues in outpatients [1][2][3][4][5][6][7][8]. Since history-taking failure and hypothesis generation failure or failure to consider the correct diagnosis are the most important contributing factors to diagnostic errors [9][10][11][12][13], they can be major targets of intervention to reduce diagnostic errors. Indeed, previous studies reported that reminding physicians of the considerable diagnoses before they started testing hypotheses increased the number of differential diagnoses and improved diagnostic accuracy irrespective of case difficulty [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, it has been noted that efforts to improve diagnostic errors have been slow due to the influence of multiple factors, including medical education, the healthcare system, and a culture of shame [14]. In addition, although there is a recent report from Japan on the analysis of diagnostic errors by residents [15], few studies have addressed diagnostic errors in Japan. In addition, regarding emergency rooms, single-center studies have quantified the cognitive biases that are likely to occur [16], but there are no quantified studies set in Japan.…”
Section: Introductionmentioning
confidence: 99%